Great Canadian Lagerstätten 3. Late Ordovician Konservat-Lagerstätten in Manitoba - Young, Graham; Rudkin, David; Dobrzanski, Edward; Robson, Sean; Cuggy, Michael; Demski, Matthew; Thompson, Deborah (Geoscience Canada, 2012)
SUMMARY Konservat-Lagerstätten, deposits in which soft-bodied or lightly sclerotized fossils are preserved, are very rare in Ordovician strata. Three significant sites are known from Upper Ordovician rocks in Manitoba: at Cat Head – McBeth Point, William Lake, and Airport Cove. These sites are in two distinct sedimentary basins: the former two are in the Williston Basin, while the latter is in the Hudson Bay Basin. All three sites contain marine fossils, but each has a different assemblage that contributes a distinct piece of the diversity picture. Important groups represented at one or more of the sites include seaweeds (algae), sponges, cnidarian medusae (jellyfish), conulariids, trilobites, eurypterids, xiphosurids (horseshoe crabs), and pycnogonids (‘sea spiders’). The different biotas reflect depositional conditions at each site. Many of the fossils are unknown elsewhere in the Ordovician at the family level or higher. The province of Manitoba therefore makes a significant contribution to knowledge of Late Ordovician biodiversity.